Blockage of Alzheimer’s gene: Breakthrough effect of Apolipoprotein E4 - Babatunde Oluwafemi Adetuyi; Peace Abiodun Olajide; Oluwakemi Semiloore Omowumi; Grace Onuwabhagbe Odine; Darasimi Deborah Okunlola; Anjolaoluwa Maryann Taiwo; Oluwaseun Dorcas Opayinka (African Journal of Advanced Pure and Applied Sciences, 2022)
One of the essential hereditary hazard factors for AD (Alzheimer’s Disease) is the existence of APOE (Apolipoprotein E4 allele). Multivariate lipoprotein called APOE happens to be crucial for the movement of cholesterol in the brain. Along with other things, it has a crucial function in the breakdown of glucose, neuro-inflammation, and neuronal signaling. The 3 Apolipoprotein allele variants include E2, E3, and E4. The most occurring allele in humans is the E3 allele. The risk of Alzheimer’s disease is connected to the E4 allele being higher, but the E2 allele is connected with a slighter risk. Building cellular and animal models has taken a lot of effort in order to comprehend the molecular processes behind APOE-related genetic risk. Results from these concepts suggest that APOE4 may increase tau development of disease in a manner similar to that of isoform-dependent and that it aggravates amyloid plaque load in a manner similar to dose-dependent